Pengaruh Kapasitas Sumber Daya Manusia dan Koordinasi Antar Lembaga Terhadap Gagal Salur Program Bantuan Sosial di Kabupaten Sabu Raiju - Fany Taruna; Riswanda Riswanda; Nursalam Nursalam (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
This study aims to analyze the influence of human resource capacity and inter-agency coordination on the failure of social assistance program distribution in Sabu Raijua Regency, a region with 3T characteristics (disadvantaged, frontier, and outermost). This study uses a quantitative associative approach. Data were collected through structured questionnaires distributed to 22 respondents directly involved in the distribution of social assistance, including officials, village officials, and program assistants. Data were analyzed using descriptive statistics and multiple linear regression. The results show that human resource capacity and inter-agency coordination, both partially and simultaneously, have a significant influence on the failure of social assistance distribution. Although the human resource capacity of program implementers is generally good in terms of procedural understanding and work experience, weaknesses were identified in digital literacy and interpersonal communication skills. Furthermore, inter-agency coordination is still hampered by data synchronization problems, weak two-way communication, and sectoral egos, which lead to delays and inaccuracies in distribution. This research recommends strengthening human resource capacity through training focused on digital technology and conflict management, as well as building an integrated data system to improve inter-agency coordination to ensure social assistance is more on target